Orientamento e inclusione: uno studio di caso nelle scuole secondarie palermitane di primo grado - Leonarda Longo (LED Edizioni Universitarie, 2017)
This paper presents the main results of the research work that promoted the design and implementation of training and guidance played in the territory of Palermo during the school years 2013/2014 and 2014/2015 in three secondary schools, with operating procedures, capable of promoting inclusive paths, based on the involvement of students, teachers and parents. The assumption from which we started is that the problems of dispersion and social marginalization can be addressed not only through direct guidance interventions with young people at risk, but also involving adults of reference because we are convinced that this will have, even at a distance of time a significant impact on students. The methodology used was that of the project-based research (D.B.R.). Totally 172 students in secondary school, 29 teachers, 171 parents participated in the research. Given the breadth and complexity of the project, due both to the number of recipients of training and guidance and the variety of activities planned, it was decided to use quantitative and qualitative instruments. The training activities and guidance were considered generally positive by students who have certainly improved their personal interest in the study.